Being the Peruvian - Peña Kolenkautsky, Saúl (2011)
Our Peru, a multicultural pluralism, multi-ethnic, mega-diverse and difficult a problem to the task of building a unified but flexible to be Peruvian challenges us to contribute to this vital task extremely arduous and complex identity, but postponed .